Effects of Hyperthermia on Telomere Length Changes in Arabidopsis thaliana Plants - I. A. Agabekian; D. Y. Sabaeva; L. R. Abdulkina (Учёные записки Казанского университета: Серия Естественные науки)
Telomeres are highly conserved nucleoprotein structures involved in the defense mechanisms of eukaryotic organisms. Their length depends on a variety of biotic and abiotic factors, such as environmental stressors. Being stationary, plants are particularly susceptible to environmental stresses. This article explores the effects of heat stress on telomere length in Arabidopsis thaliana. Telomere length was measured for individual chromosome arms. It was shown that hyperthermia at 42 °C altered telomere length in some chromosome arms of the wild-type A. thaliana plants, as well as in the long telomeres of the knockout mutants for the gene OLI5/RPL5A. The high temperatures caused the telomeres to become shorter, with the longer telomeres showing a stronger response to the stress. This suggests that the complex regulation of telomere length may be associated with exposure to environmental stressors.